PRICE AND BRAND NAME AS INDICATORS OF QUALITY DIMENSIONS FOR GENERIC DRUGS - , Christian Budiman Urbanus ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Health care expenditures are one of the biggest concerns for many countries, including Indonesia, and the introduction of generic drug can lead to significant savings as drugs make up a large portion of health budgets. However, Indonesian consumersâ preference of branded drug over generic drug is remain unchanged. Indonesian consumers generally perceived generic drug is of low quality mainly because of its low price. Widely known as price-quality inferences, this process happens when consumers use price (and other extrinsic cues as well) as a signal of quality. This research investigated the Indonesian consumer definition of drugâs quality, the use of extrinsic cues as an indicator of drug quality, the moderating effect of consumer knowledge to the consumerâs inference process, and the influence of perceived quality to the purchase intent. This research is a two-stage study, involving two studies run consecutively. The first study is a qualitative and descriptive study on Indonesian consumersâ definition of drugs quality. Three qualitative study methodologies (literature review, focus group discussion, and in-depth interview) employed and being analyzed using content analysis. The results then elaborated into academically-sound quality dimensions of drug. While for the second study which is a quantitative and explanatory study, the relationship of the variables involved (price, brand name, consumer knowledge, quality dimensions, and purchase intent) is studied. The second study employed multivariate regression analysis with moderating factor to study the relationship and test the hypotheses. A survey was done in order to collect primary data for the second study. The result from the first study revealed four consumer-defined quality dimensions of drugs: safety, efficacy, acceptability, and availability. In the second study, brand name is proven to influences the perceived quality of generic drug. The perceived quality influences consumersâ purchase intent which decides their actions and behaviors in the marketplace. This suggests Indonesiaâs policy maker of generic drug to strengthen generic drugâs brand equity based through reassurance of its safety, efficacy, acceptability, and availability instead of promoting its low price.